PENGARUH APLIKASI GA3 TERHADAP PEMBUNGAAN TANAMAN Anthurium andreanum cv. AVO CUBA - Bambang S. Purwoko; Dyah Sri Sulistiyani; Livy W. Gunawan (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1997)
The objective of the research was to determine the effect of GA3 application on the flowering of Anthurium andreanum cv. Avo Cuba. The experiment consisted of two factors namely dosage and frequency of application: once or twice with one half dosage each. The result showed that GA3 increased leaf area, length of flower stalk, and the number of flower produced, shortened the time of flower emergence and harvest date. GA3 did not influence flower size and vase life. The frequency of application had no effect on Anthurium flowering. There was no interaction of dosage and frequency of application. Dosage of GA3 at 10 mg per plant gave good effect on reproductive characteristics.